Antinutritional Factors of Seed, Seed Hull, and Pod, of African Locust Bean (Parkia Biglobosa) - Jacob, Mathew; Amuda, A. J.; Umaru, Isaac John (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Parkia biglobosa (African locust bean), is a genus of flowering plants of the Fabaceae family and is one of the many species of trees which serve as sources of food and medicinal purposes to the indigenous people of Africa. It is a perennial deciduous tree and provides shade for man. The research work was carried out in the Department of Animal Production and Health, Faculty of Agriculture and Life Sciences Federal University Wukari laboratory. The samples of different part of African locust bean (Parkia biglobosa) tree were collected within the University environment. The different part collected were as follows: Seed, Seed Hull, and Pod and each one serve as a treatment (T1...T3). Samples collected were oven dried and milled for laboratory analysis to determine the anti-nutritional factors (ANFs) using standard techniques. The following anti-nutritional factors were determined: Saponin, Tannin, Phytate, Alkaloids, Oxalate, Phenol, Lectin, Flavonoids and Cyanin. Data obtained were subjected to analysis of variance (ANOVA) using SPSS version 23.0.2018. The results of analysis showed that all the ANFs (Saponin (0.21-0.24%), Tannin (0.02-0.07%), Phytate (0.31-0.32%), Alkaloids (0.24-0.29%), Oxalate (0.20-0.24%), Phenol (0.15-0.29%), Lectin (51.94-78.28 Lu/mg), Flavonoids (0.004-0.007%) and Cyanin (5.28-11.40 mg/kg) observed varied significantly (p<0.05) across the treatments, such that T3 (pod) had the highest values in all the ANFs while the T1 (Seed) had the lowest value except for saponin and Lectin. However, T1 in oxalate and flavonoids and T3 in alkaloids respectively. In conclusion the anti-nutritional factors of the African locust bean (Parkia biglobosa) tree parts, were lower than the tolerance level. Consequently, ruminant farmers can include pod in formulating ration for their livestock.